(3TQM ThGgO bWQ GdfOis - (3GdCYQLj, UGOb GdMSjfj GdCYQLjs
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY bOQ GdYdeGA(B... (3hHYO ajbhd(B... (3deG cGf cJGH GdEeGe(B... (3GHf gTGe(B... (3bO Ye PcQg aj SGFQ GdCeUGQ (B... (3hcGfJ ThGgO GdTYQjI dG JNdhG Yf ZehV(B...s
(3BNQgG (B:s
(3hCbGSe(B: (3eVGQY eLRhe aj LhGH GdCeQ haGYdgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs